Contents of lobetyolin, syringin, and atractylolide III in Codonopsis pilosula are related to dynamic changes of endophytes under drought stress - Yichuan Liang; Guangfei Wei; Kang Ning; Guozhuang Zhang; Youping Liu; Linlin Dong; Shilin Chen (BMC, 2021)
Abstract Background Codonopsis pilosula, an important medicinal plant, can accumulate certain metabolites under moderate drought stress. Endophytes are involved in the metabolite accumulations within medicinal plants. It is still unknown that the endophytes of C. pilosula are associated with the accumulations of metabolites. This study aims to investigate the promoting effect of endophytes on the accumulations of active substances in C. pilosula under drought stress. Methods High-performance liquid chromatography and high-throughput sequencing technology were performed to investigate changes in the contents of secondary metabolite and endophyte abundances of C. pilosula under drought stress, respectively. Spearman's correlation analysis was further conducted to identify the endophytic biomarkers related to accumulations of pharmacodynamic compounds. Culture-dependent experiments were performed to confirm the functions of endophytes in metabolite accumulations. Results The distribution of pharmacological components and diversity and composition of endophytes showed tissue specificity within C. pilosula. The contents of lobetyolin, syringin, and atractylolide III in C. pilosula under drought stress were increased by 8.47%‒86.47%, 28.78%‒230.98%, and 32.17%‒177.86%, respectively, in comparison with those in untreated groups. The Chao 1 and Shannon indices in different parts of drought-stressed C. pilosula increased compared with those in untreated parts. The composition of endophytic communities in drought treatment parts of C. pilosula was different from that in control parts. A total of 226 microbial taxa were identified as potential biomarkers, of which the abundances of 42 taxa were significantly and positively correlated to the pharmacodynamic contents. Culture-dependent experiments confirmed that the contents of lobetyolin and atractylolide III were increased by the application of Epicoccum thailandicum, Filobasidium magnum, and Paraphoma rhaphiolepidis at the rates of 11.12%‒46.02%, and that the content of syringin was increased by Pseudomonas nitroreducens at the rates of 118.61%‒119.36%. Conclusions Certain endophytes participated in the accumulations of bioactive metabolites, which provided a scientific evidence for the development and application of microorganisms to improve the quality of traditional Chinese medicine.